Handwriting and Dysgrafia: Relation and Assessment - Capellini, Simone Aparecida [UNESP]; Cardoso, Monique Herrera [UNESP] (My University, 2018)
Handwriting and Dysgrafia: Relation and Assessment presents (in eleven chapters no less) the interdisciplinary perspective and relation between handwriting and dysgraphia. Therefore, in organizing this e-book, the authors think about how it would be possible, through their experiences with the care of students with dysgraphia complaints in the Investigation Learning Disabilities Laboratory at the Speech and Hearing Sciences Department (São Paulo State University Júlio de Mesquita Filho - UNESP - Marília, São Paulo, Brazil), to assist educators as well as health and education professionals to broaden their knowledge of the clinical and educational characteristics of students with dysgraphia.